2021
DOI: 10.3390/ani11020350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soybean Oil Supplementation on Milk Production, Digestibility, and Metabolism in Dairy Goats under Thermoneutral and Heat Stress Conditions

Abstract: In a previous work, we observed that heat-stressed goats suffer reductions in milk yield and its contents of fat and protein. Supplementation with soybean oil (SBO) may be a useful strategy to enhance milk quality. In total, eight multiparous Murciano–Granadina dairy goats (42.8 ± 1.3 kg body weight; 99 ± 1 days of lactation) were used in a replicated 4 × 4 Latin square design with four periods; 21 d each (14 d adaptation, 5 d for measurements and 2 d transition between periods). Goats were allocated to one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
2
2
0
Order By: Relevance
“…The greater EE digestibility in SFO and OCT goats was expected in this study, because with the higher EE digestibility, the animals will have more energy to supply body requirements and compensate the daily loss of energy via milk. Hamzaoui et al (2021) reported that oil supplementation in the diet did not affect the N retention of goats, and our study detected the similar result. This may be explained partly that after dissociation of the tannin-protein complex, the tannins released in the abomasum can bind again to the non-degraded proteins in the rumen (Naumann et al, 2017), microbial proteins or endogenous proteins when they reach in the small intestine (Waghorn, 2008).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The greater EE digestibility in SFO and OCT goats was expected in this study, because with the higher EE digestibility, the animals will have more energy to supply body requirements and compensate the daily loss of energy via milk. Hamzaoui et al (2021) reported that oil supplementation in the diet did not affect the N retention of goats, and our study detected the similar result. This may be explained partly that after dissociation of the tannin-protein complex, the tannins released in the abomasum can bind again to the non-degraded proteins in the rumen (Naumann et al, 2017), microbial proteins or endogenous proteins when they reach in the small intestine (Waghorn, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…That no change of total DM intake in this study was supported by some previous studies, in which soybean oil was supplemented at 2 to 5% DM in the diets of dairy goats (Bouattour et al, 2008;Mele et al, 2008;Hamzaoui et al, 2021) and cows (Qin et al, 2020). Nutrient intakes such as DM, OM, CP, NDF, ADF, GE, ME were not affected by the experimental diets.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Extreme environmental conditions affect the accessibility of goat farmers to appropriate pastures (Marino et al, 2015). Heat stress can negatively affect milk yield and the contents of total protein, casein, and fat of milk in goats (Sevi et al, 2001;Hamzaoui et al, 2012;Salama et al, 2014). Marino et al (2015) emphasized that even if the goat was a heat-tolerant species, climate change and other stress factors result in the impairment of production and reproduction performance.…”
Section: Introductionmentioning
confidence: 99%